2015
DOI: 10.1007/s00204-015-1538-1
|View full text |Cite
|
Sign up to set email alerts
|

Dual effect of red wine on liver redox status: a concise and mechanistic review

Abstract: Chronic ethanol consumption is a strong risk factor for the development of liver disease. Multiple mechanisms are involved in ethanol-mediated liver injury; oxidative stress being pointed has an important factor. However, it should be noted that moderate consumption of red wine has been associated with hepatoprotective effects, mainly due to the antioxidant effect of resveratrol, one of its polyphenolic compounds. In this paper, the potential molecular mechanisms through which the protective effects of resvera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 126 publications
0
11
0
Order By: Relevance
“…Cigarette smoking reduces the levels of SOD through the elevation of hydrogen peroxide which inactivates SOD. Since resveratrol elevates the levels of SOD, this would reduce oxidative stress and attendant destruction of tissues related to this condition . Resveratrol has also been shown to upregulate production of the transcription factor, Nrf2 (nuclear factor erythroid 2‐related factor 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cigarette smoking reduces the levels of SOD through the elevation of hydrogen peroxide which inactivates SOD. Since resveratrol elevates the levels of SOD, this would reduce oxidative stress and attendant destruction of tissues related to this condition . Resveratrol has also been shown to upregulate production of the transcription factor, Nrf2 (nuclear factor erythroid 2‐related factor 2).…”
Section: Discussionmentioning
confidence: 99%
“…SMK+PLAC oxidative stress and attendant destruction of tissues related to this condition. [79][80][81][82][83] Resveratrol has also been shown to upregulate production of the transcription factor, Nrf2 (nuclear factor erythroid 2-related factor 2). Nrf2 is an important modulator of the antioxidant response which regulates the expression of antioxidant genes including SOD.…”
Section: Concentration Of Nadph (Pmol/mg)mentioning
confidence: 99%
“…Moreover, oxidative stress is associated with ageing [10,11] and life-style factors, such as excessive alcohol consumption [12] and cigarette smoking [13,14]. However, there is growing evidence that reactive oxygen species (ROS) may play a possible physiological role as redox signalling messengers for some regulatory functions [15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported the hepato and renal protective effects of S. cumini fruit, red wine and polyphenols of Jamun fruit and red wine, respectively. [37][38][39] It has been found that in mice S. cumini pulp extract decreases bile duct ligation induced inflammation and oxidative stress in addition to providing protection against hepatocellular injury. 40 Similarly, significant reductions in liver marker enzymes were observed after 14 weeks of fruit extract administration to hyperlipidemic animals and the authors ascribed the presence of flavonoids for the observed liver protective activity.…”
Section: Discussionmentioning
confidence: 99%